2009
DOI: 10.1245/s10434-009-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Size in T3 Gastric Cancer

Abstract: Tumor size is a simple and reliable prognostic factor for patients with T3 gastric cancer; it might be a candidate for the gastric cancer staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Maximum tumor diameter >8 cm was associated with significantly poorer OS than maximum diameter <8 cm [22]. Errors may occur, however, when classifying tumor size without considering the effects of invasion depth and lymph node metastasis on tumor size [23]. It is difficult to identify the most important prognostic factors because many variables are interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum tumor diameter >8 cm was associated with significantly poorer OS than maximum diameter <8 cm [22]. Errors may occur, however, when classifying tumor size without considering the effects of invasion depth and lymph node metastasis on tumor size [23]. It is difficult to identify the most important prognostic factors because many variables are interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…8 Liu et al found tumor size to be an independent prognostic factor for patients with T3 gastric cancer in the 6th edition system, and the 5-year survival rates were 29.5 and 42.7% in the large-size (LSG, tumor [6 cm) and small-size groups (SSG, tumor B6 cm), respectively (P = 0.045). 9 Secondly, the subdivision of N classification based on the number of metastatic lymph nodes was changed. The N1 substage in the old system was divided into N1 and N2 in the new system, and N2 and N3 substages were merged into N3.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was impossible to precisely predict the prognosis through the conventional staging procedures as a result of the variability of prognosis within the same stage of gastric cancer. Liu et al [5] found that there were significant differences between the largersize tumor group and the small-size tumor group according to stage IIIb and IV. Therefore, it was essential to search for the other specific factors to identify subgroups of patients with more aggressive course of the disease especially in the 7th editions of the UICC TNM Staging System.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was essential to search for the other specific factors to identify subgroups of patients with more aggressive course of the disease. Recently, some studies have shown that other pathological factors, such as the number of positive lymph nodes, the presence of extracapsular lymph node involvement, and tumor size had additional prognostic value [3][4][5]. Given that some biological markers, such as oncogenes, tumor-suppressor genes, cell-cycle regulators, and DNA repair genes, were related to tumor genesis, growth, invasion and metastasis, many scientists were dedicated to searching for the new prognostic factors with these molecular markers.…”
Section: Introductionmentioning
confidence: 99%